Faktor -Faktor yang memengaruhi Peningkatan Daya Saing Klaster Mebel di Kabupaten Jepara - Utami Handayani, Naniek; Santoso, Haryo; Ichwal Pratama, Adithya (Department Industrial Engineering, University of Muhammadiyah Malang, 2012)
Indonesia is known as one of the nation's largest mebel exporter in the world. But, the development of Central Java mebel exports for four years fluctuated but tended to decline that was caused by economic crisis of the world. Industrial clusters are one of the strategic that was used to develop industry based on region. The purpose of this study was to analyze the factors affecting the competitiveness of the mebel industry in order to take policies that can be used to improve the competitiveness of Indonesian mebel industry of Central Java especially in overseas markets. This study use PLS (Partial Least Square) as tools that serve to test the diamond model porter plus social capital variables and analyze the factors that affect competitiveness, caused total population size used in this study is small. The results showed that competitiveness in the Mulyoharjo furniture cluster is influenced by condition factors, demand condition, related supporting industries. Whereas, Senenan furniture cluster is influenced by condition factors, the role of government, the opportunities, and social capital.